Hubungan Penggunaan Kombinasi Golongan Antidiabetes dan Antihipertensi Terhadap Kejadian Interaksi Obat Pada Pasien BPJS - Annis Rahmawaty; Rika Agustina; Heni Setyoningsih; Rifda Naufa Lina (LPPM Universitas Abdurrab, 2023)
Diabetes mellitus and hypertension are chronic diseases that require long-term therapy, patients will receive a combination of more than two types of drugs. Therapy with two or more types of drugs can cause drug interactions that have an impact on the patient's treatment. Chronic complications can affect body organs, including morbidity and mortality. The aim of this study was to determine the incidence of drug interactions when using a combination of antidiabetic and antihypertensive drug classes and to determine the relationship between the use of a combination of antidiabetic and antihypertensive drug classes on the incidence of drug interactions. This research was conducted prospectively on drug prescriptions for type 2 diabetes mellitus patients with hypertension in BPJS referral patients at Waras Purwodadi Pharmacy. A total of 51 samples were obtained. Data were analyzed descriptively to see the incidence of drug interactions using Stockley's Drug Interactions Eight Edition 2008, Drug Interaction Facts 2009, Medscape Drug Interaction Checker Application, and Drug Interaction Checker (Drugs.com). Data analysis was analyzed using SPSS using the Chi-Square test. There were drug interactions in 44 prescriptions (86.3%) and there were no drug interactions in 7 prescriptions (13.7%). The results of the Chi-Square test showed that there was a relationship between the use of combination of antidiabetic and antihypertensive drug of classes on the incidence of drug interactions in BPJS patients, with a value of P = 0.000 (P < 0.05). The conclusion is that there is a significant relationship Between The Use of Combination Antidiabetic and Antihipertensive drug of Classes On The Incidence Of Drug Interaction In BPJS Patients